Determinants involved in regulating the proportion of edited apolipoprotein B RNAs. - Sowden, M (1996)
Editing the apolipoprotein B (apoB) RNA involves deamination of cytidine by the catalytic subunit, APOBEC-1, as a component of an editosome. A tripartite sequence (editing motif) is essential for editosome assembly and site-specific editing. Current theory for the regulation of apoB RNA editing proposes that APOBEC-1 is rate limiting in cells and determines the proportion of edited apoB mRNAs. An evaluation of how the overexpression of APOBEC-1 increased the proportion of edited RNAs has led to the discovery of a paradox. McArdle cells edit a constant proportion of apoB RNA regardless of the total number of apoB RNAs expressed. Despite virtually identical editing motifs, apoB RNA transcripts from the endogenous gene and transfected, exogenous cDNA were edited with characteristic, but different efficiencies. This suggested that these RNAs were interacting with the editing machinery as distinct and noncompeting populations. We evaluated whether the presence of introns in the endogenous transcript may have distinguished it as a distinct population having reduced editing efficiency. The editing efficiency of chimeric splicing-editing RNA substrates was highest on fully processed RNA. Increased exon length improved utilization of the editing motif in these chimeric constructs. Taken together, the data suggest that the close proximity of introns can reduce apoB RNA editing efficiency. A population "gating" hypothesis is proposed wherein the proportion of edited RNAs in a population is determined my multiple cis- and trans-acting factors as RNAs pass through a nuclear restriction point.